Catalytically inactive DNA ligase IV promotes DNA repair in living cells. Issue 19 (20th October 2022) - Goff, Noah J; Brenière, Manon; Buehl, Christopher J; de Melo, Abinadabe J; Huskova, Hana; Ochi, Takashi; Blundell, Tom L; Mao, Weifeng; Yu, Kefei; Modesti, Mauro; Meek, Katheryn
Abstract: DNA double strand breaks (DSBs) are induced by external genotoxic agents (ionizing radiation or genotoxins) or by internal processes (recombination intermediates in lymphocytes or by replication errors). The DNA ends induced by these genotoxic processes are often not ligatable, requiring potentially mutagenic end-processing to render ends compatible for ligation by non-homologous end-joining (NHEJ). Using single molecule approaches, Loparo et al. propose that NHEJ fidelity can be maintained by restricting end-processing to a ligation competent short-range NHEJ complex that 'maximizes the fidelity of DNA repair'. These in vitro studies show that although this short-range NHEJ complex requires DNA ligase IV (Lig4), its catalytic activity is dispensable. Here using cellular models, we show that inactive Lig4 robustly promotes DNA repair in living cells. Compared to repair products from wild-type cells, those isolated from cells with inactive Lig4 show a somewhat increased fraction that utilize micro-homology (MH) at the joining site consistent with alternative end-joining (a-EJ). But unlike a-EJ in the absence of NHEJ, a large percentage of joints isolated from cells with inactive Lig4 occur with no MH – thus, clearly distinct from a-EJ. Finally, biochemical assays demonstrate that the inactive Lig4 complex promotes the activity of DNA ligase III (Lig3).